2021
DOI: 10.1111/jjns.12404
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to perceived control and health‐related quality of life of patients after acute coronary syndrome during admission and after discharge

Abstract: Aim To explore the relationship between demographic factors, acute coronary syndrome‐related factors, perceived control and health‐related quality of life during admission, 3 months and 6 months after discharge, in patients with acute coronary syndrome. Methods Participants were recruited for this longitudinal study after admission for acute coronary syndrome in three university hospitals in the Tokyo metropolitan area, Japan. Self‐administered questionnaires included demographic data, perceived control, healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…These results indicate that nationality is a stronger predictor of preventive health behavior than perceived control, as also indicated in odds ratios. Actually, previous studies reported weaker association between perceived control and health outcomes in Japanese elderly people than American elderly people (53,54), an outcome that was consistent with young adults in this study. This can be one reason why Japanese students showed the lowest perceived control but the highest preventive behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicate that nationality is a stronger predictor of preventive health behavior than perceived control, as also indicated in odds ratios. Actually, previous studies reported weaker association between perceived control and health outcomes in Japanese elderly people than American elderly people (53,54), an outcome that was consistent with young adults in this study. This can be one reason why Japanese students showed the lowest perceived control but the highest preventive behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Since preventing infection is closely intertwined with government policies and strategies, students who are aware of those policies or are politically active may have higher preventive behaviors. Although previous studies have shown that Japanese people have lower levels of perceived control than people in any other countries, 31,32 this study found that students' perceived control was comparable with that of Salehi et al's 18 participants of young Iranian women.…”
Section: H1: Nursing Students With Higher Perceived Control Practice ...contrasting
confidence: 60%
“…Cronbach α of the Japanese version with 137 patients with ACS was 0.822. 11 In the current study, Cronbach α was adequate at 0.794.…”
Section: Measurementmentioning
confidence: 50%
“…The FSI was originally created to measure fatigue in patients with cancer, and reliability ( α > .90) and validity were confirmed 32 . It has been used successfully for patients with coronary heart disease, 33 including Japanese patients 11 . It is a publicly available instrument that does not require permission to use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation